A Perspective on a Possible Relation Between the Psychopathology of the Schizophrenia/Schizoaffective Spectrum and Unconjugated Bilirubin: A Longitudinal Protocol Study - Gama Marques, João; Arantes-Gonçalves, Filipe (Frontiers in Psychiatry, 2018)
Some authors suggest a relation between Unconjugated Bilirubin (UCB) plasma high levels and schizophrenia, as schizophrenia patients have been showing higher UCB levels when compared with other psychiatric patients and general population. These higher UCB levels have been already correlated with acute psychotic states, positive symptoms, and poor outcome in patients with schizophrenia. Schizophrenia and schizoaffective disorders share common symptoms but there aren't yet accepted biomarkers for their distinction. In our study protocol we propose an observational longitudinal study on a sample composed of two subgroups: patients with schizophrenia and patients with schizoaffective disorder. We will compare the UCB levels between groups, and search for a possible correlation with patient's psychopathology. For that purpose we will use nosological, psychopathological, neuropsychological, and psychosocial instruments. Thus we will be testing two different hypotheses: (1) Is UCB serum level a diagnosis indicator, with categorical distinction potential, between groups of patients with different psychotic disorders? (2) Is UCB serum level a severity indicator, with dimensional distinction potential, among groups of patients with the same psychotic disorder? We believe that UCB mean levels may contribute to some clarification of this controversy, as a potential biological indicator, facilitating the distinction between these two diagnostic categories anddiscriminating the dimensional severity among each of these psychotic conditions. Thus we may be opening a new opportunities for innovative and exciting biological psychiatry research regarding organic aspects in the schizophrenia spectrum.